One new species of the genus Nigrimacula Shi, Bian & Zhou, 2016 (Orthoptera: Meconematinae) from Sichuan, China - Wang, Hai-Jian; Shi, Fu-Ming (Zootaxa, 2016)
The paper describels one new species, i.e. Nigrimacula sichuanensis Wang & Shi, sp. nov. from Sichuan, China, and provides photographs of morphological characters. The type material is deposited in the Museum of Hebei University.